The diagnosis and treatment of cardiac lymphangioma: A case report and literature review. Issue 2 (January 2019) - Diao, Wen-Jie; Shi, Chao; Liu, Ge; Liu, Xue-Gang; Li, Hai-Hui; Meng, Jin-Jin; Shi, Yu; Chang, Ming-Ming; Liu, Yi-Yao
Abstract: Rationale: Cardiac lymphangioma is a rare disease. Until now, there have been only a few cases of cardiac lymphangioma reported in the literature. Patient concerns: We report the case of a 57-year-old female patient with cardiac lymphangioma from atrial septum. Diagnosis: Color Doppler echocardiography was performed, which revealed a tumor occupying a large amount of space in the left and right atrium. Interventions: The patient underwent thoracoscopic cardiac tumor resection under general anesthesia according to the procedure used for benign tumors. Outcomes: The patient recovered completely and was discharged home. Follow-up color Doppler echocardiography scans obtained from 6 months to 2 years after the operation showed no recurrent mass. Lessons: Once the tumor is detected, surgical treatment should be implemented as soon as possible.